Survey on Compliance with Preoperative Preparation Procedures for Elective Surgery at Vinmec Central Park International General Hospital, 2025 (Vietnam Journal of Community Medicine, 2026)
Background: Preoperative patient preparation is a critical step in ensuring surgical safety. This study aimed to survey the compliance with the preoperative preparation and handover protocol for elective surgical patients at Vinmec Central Park International General Hospital.Objectives: To survey the compliance with the preoperative preparation protocol for elective surgical patients.Methods: A cross-sectional descriptive study was conducted on 120 patients from January to June 2025, using observation checklists and interviews.Results: The average compliance rate was high: 99.6% for documentation procedures and 98.9% for patient handover. Core items (surgical consent, laboratory tests, pre-anesthesia assessment, jewelry removal, identification bands, allergy screening, fluid fasting) achieved 100%. However, some items showed limitations: correct bathing technique (83.3%), appropriate hair removal (13.3% not performed despite indication), surgical site marking (only 35.8% performed), and complete signatures (97.5%). Statistically significant differences were found between departments for signature completion (p=0.037), hair removal (p
Keywords: Preoperative preparation, patient handover, protocol compliance, surgical safety.